High "fitness age" as a risk factor for morbidity and premature mortality - Novák, Jaroslav; Štork, Milan (Physiological research, 2023)
The level of cardiorespiratory capacity, as measured by maximum VO(2)max oxygen consumption, is a significant factor related to the risk of metabolic syndrome, coronary heart disease and other health disorders. A total cohort of 2901 examinations was divided into 5 groups according to the nature of physical activity: group A - endurance athletes, group B - team sports players, group C - other competitive athletes, group D - recreational leisure-time athletes, group E - people with health problems. Cardiorespiratory fitness was assessed according to the VO(2)max and METmax parameters found in the stress test on a bicycle ergometer. A gradually increased load until exhaustion was used. While in groups A to D cases that would be classified as NYHA 1 (METmax lower than 9) were quite rare (10 cases out of 2777, i.e. 0.3 %), in groups E it was 20 % in men (16 cases out of 82) and 52 % in women (23 cases out of 44) of those examined. Accordingly, fitness age in groups A, B and C generally corresponded to a lower age than the calendar age, in groups E of both men and women, fitness age was significantly higher compared to the calendar age. High fitness age represents a significant risk of morbidity in relation to non-communicable diseases and probably also a significant limitation of their quality of life in later age.
Keywords: Female; ženské pohlaví; Physical Fitness; tělesná výkonnost; kvalita života; Morbidity; Oxygen Consumption; lidé; cvičení; Risk Factors; Mortality, Premature; Male; rizikové faktory; mužské pohlaví; Exercise; morbidita; Quality of Life; spotřeba kyslíku; předčasná smrt; Humans